Conductive ceramic and preparation method and application thereof
By setting a ceramic coating with a special structure on the surface of the conductive ceramic substrate, the problems of reduced performance and shortened service life of conductive ceramics during high-temperature heating are solved, and structural stability and heating uniformity are improved.
Patent Information
- Application Number
- CN202311232036.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-03-21
AI Technical Summary
During the high-temperature heating process of existing conductive ceramics, the metal components are prone to oxidation, resulting in reduced performance and shortened service life. The thermal expansion coefficients between the ceramic coating and the substrate are large, resulting in heating unevenness and structural failure.
A special structured ceramic coating is provided on the surface of the conductive ceramic matrix, which consists of a base layer and a surface layer containing components similar to the matrix to reduce the coefficient of thermal expansion, and a glass phase and metal complex to provide antioxidant and self-healing capabilities.
It effectively improves the structural stability and heating uniformity of conductive ceramics, extends service life, and improves the antioxidant performance and crack self-repair ability.
Smart Images

Figure CN119661253A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of ceramic materials, and in particular to a conductive ceramic and a preparation method and application thereof. Background Art
[0002] At present, conductive ceramics are widely used in heat-not-burn heating elements. However, during the high-temperature heating process, the metal components of existing conductive ceramic products will be exposed to the air and oxidized, and cracks are easily generated on the surface, which leads to a decrease in product performance and a shortened service life. In order to increase the service life of conductive ceramics, the industry usually introduces an anti-oxidation ceramic coating to protect the conductive ceramic substrate. However, the thermal expansion coefficients between the existing ceramic coatings and the conductive ceramic substrate components are quite different, and structural failures are prone to occur during the heating process. The heating uniformity is reduced, which affects the overall performance of the heat-not-burn heating element. Therefore, it is necessary to provide a ceramic coating that can thermally match the conductive ceramic substrate while exerting an anti-oxidation effect, thereby improving the structural stability and heating uniformity of the conductive ceramic. Summary of the invention
[0003] In view of this, the present application provides a conductive ceramic, a preparation method and an application. The conductive ceramic has a ceramic coating with a special structure on the surface of a conductive ceramic substrate. The difference in thermal expansion coefficient between the ceramic coating and the conductive ceramic substrate is small, the antioxidant ability is excellent, and the ceramic coating has the ability to self-repair cracks. The conductive ceramic is used for the preparation of a heat-not-burn heating element, which can effectively improve the performance and service life of the heating element.
[0004] In a first aspect, the present application provides a conductive ceramic, comprising a conductive ceramic substrate and a ceramic coating arranged on the surface of the conductive ceramic substrate, wherein the conductive ceramic substrate comprises a metal element, and the ceramic coating comprises a bottom layer and a surface layer sequentially stacked on the surface of the conductive ceramic substrate; the bottom layer comprises a silicon-containing material, a boron-containing material and at least one phosphate of the metal element, and the surface layer comprises a glass phase and a metal complex.
[0005] In an embodiment of the present application, the surface layer contains at least one of the metal elements, as well as silicon, boron, phosphorus and oxygen.
[0006] In an embodiment of the present application, the metal element contained in the surface layer is the same as the metal element contained in the bottom layer.
[0007] In an embodiment of the present application, in the surface layer, the glass phase content on the side away from the conductive ceramic substrate is greater than the glass phase content on the side close to the conductive ceramic substrate, and the metal complex content on the side close to the conductive ceramic substrate is greater than the metal complex content on the side away from the conductive ceramic substrate.
[0008] In an embodiment of the present application, the metal element includes one or more of aluminum, magnesium and transition metals; the transition metal includes one or more of gold, silver, copper, platinum, nickel, chromium, yttrium, cobalt, zinc, molybdenum and manganese;
[0009] The silicon-containing material includes one or more of elemental silicon, molybdenum disilicide, silicon carbide and silicon nitride;
[0010] The boron-containing material includes one or more of elemental boron, boron oxide, boron carbide, boron nitride and zirconium boride.
[0011] In an embodiment of the present application, the glass phase and the metal complex of the surface layer are obtained by reacting the same silicon-containing material and boron-containing material as the bottom layer and at least one phosphate of the metal element in an oxidizing atmosphere.
[0012] In the embodiment of the present application, the bottom layer includes 10%-50% by mass of the silicon-containing material, 10%-30% by mass of the boron-containing material, and 30%-70% by mass of the phosphate of the metal element.
[0013] In the embodiment of the present application, the thickness of the ceramic coating is 30 μm-100 μm, the thickness of the surface layer is 10 μm-35 μm, and the thickness of the bottom layer is 20 μm-65 μm.
[0014] In the embodiment of the present application, the electrical conductivity of the ceramic coating is less than or equal to 10 -12 S / cm; the bonding strength between the conductive ceramic substrate and the ceramic coating is greater than or equal to 5MPa; the porosity of the conductive ceramic is less than or equal to 0.1%; the mass change rate of the conductive ceramic after heating at 300°C-1000°C for 2h is less than or equal to 0.1%.
[0015] The conductive ceramic provided in the present application is provided with a ceramic coating with a special structure on the surface of the conductive ceramic substrate. The bottom layer components in the ceramic coating are similar to the ceramic substrate components, and the difference in thermal expansion coefficients between the two is small, which can alleviate the thermal mismatch effect caused by the large difference in thermal expansion coefficients between the ceramic coating and the conductive ceramic substrate, and at the same time enhance the bonding ability between the ceramic coating and the conductive ceramic substrate; the surface layer of the ceramic coating provides excellent antioxidant properties and coating crack self-repairing ability, further alleviates the thermal mismatch effect, and improves the comprehensive performance and service life of the conductive ceramic.
[0016] In a second aspect, the present application provides a method for preparing a ceramic coating, comprising:
[0017] Prepare a mixed slurry with silicon-containing material, boron-containing material and phosphate of metal elements, and apply the mixed slurry on the surface of the conductive ceramic substrate;
[0018] The conductive ceramic substrate coated with the mixed slurry is subjected to oxidation treatment to obtain a conductive ceramic with a ceramic coating.
[0019] In the embodiment of the present application, the temperature of the oxidation treatment is 1000° C.-1500° C., and the time of the oxidation treatment is 1 h-5 h.
[0020] The coating preparation method provided in the present application is novel, the preparation process is simple, and the prepared product has excellent performance.
[0021] In a third aspect, the present application provides a heat-without-combustion heating element, wherein the heat-without-combustion heating element comprises the conductive ceramic described in the first aspect or the conductive ceramic prepared by the preparation method described in the second aspect.
[0022] The heating element provided in the present application has good structural stability, good heating uniformity and excellent overall performance.
[0023] In a fourth aspect, the present application provides an electronic cigarette, comprising the heat-without-combustion heating element described in the third aspect.
[0024] The electronic cigarette provided by the present application has excellent comprehensive performance, long service life and strong product competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the embodiments or the prior art description. The specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0026] Figure 1 A schematic cross-sectional view of a conductive ceramic 100 provided in one embodiment of the present application;
[0027] Figure 2 A schematic diagram of the formation mechanism of a metal complex provided in one embodiment of the present application;
[0028] Figure 3 This is a schematic diagram of a bonding strength test of a ceramic coating 20 on the surface of a conductive ceramic 100 in one embodiment of the present application;
[0029] Figure 4 A flow chart of a method for preparing a conductive ceramic 100 provided in one embodiment of the present application;
[0030] Figure 5 This is a cross-sectional scanning electron microscope image of the conductive ceramic prepared in Example 1 of the present application;
[0031] Figure 6 for Figure 5 The X-ray diffraction analysis results of the area in the middle dotted box;
[0032] Figure 7 for Figure 5 Line scanning analysis results of oxygen element in ceramic coating;
[0033] Fig. 8A and Figure 8B The following are the scanning electron microscope images of the ceramic coating crack before and after repair. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0035] In the related technology, conductive ceramics mainly achieve oxidation resistance through the ceramic coating on the surface of the conductive ceramic substrate. The ceramic coating is mostly composed of a glass phase. However, there are significant differences in the physical properties between the glass phase component and the conductive ceramic substrate component, resulting in a large difference in the thermal expansion coefficient between the ceramic coating and the conductive ceramic substrate. This aggravates the thermal mismatch effect during high-temperature heating, causes cracks on the surface of the ceramic coating, weakens the conductive performance of the conductive ceramic, and greatly reduces the service life.
[0036] In order to solve the above technical problems, the conductive ceramic is provided with a ceramic coating with a special structure on the surface of the conductive ceramic substrate. The difference in thermal expansion coefficient between the ceramic coating and the conductive ceramic substrate is small, the anti-oxidation ability is excellent, and the ceramic coating has the ability to self-repair cracks. The conductive ceramic is used for the preparation of heat-not-burn heating elements, which can effectively improve the performance and service life of the heating elements.
[0037] See also Figure 1 , Figure 1This is a cross-sectional schematic diagram of a conductive ceramic 100 provided in one embodiment of the present application. The conductive ceramic 100 includes a conductive ceramic substrate 10 and a ceramic coating 20 arranged on the surface of the conductive ceramic substrate 10. The ceramic coating 20 includes a bottom layer 21 and a surface layer 22 stacked in sequence on the surface of the conductive ceramic substrate 10. The bottom layer 21 is stacked in contact with the conductive ceramic substrate 10, and the surface layer 22 is arranged on a side surface away from the conductive ceramic substrate 10. Among them, the bottom layer 21 includes silicon-containing materials, boron-containing materials and phosphates of at least one of the metal elements. The bottom layer 21 uses a material with a thermal expansion coefficient as close as possible to the conductive ceramic substrate 10, which can reduce the difference in thermal expansion coefficient between the bottom layer 21 and the conductive ceramic substrate 10, alleviate the thermal mismatch effect of the conductive ceramic 100, and improve the bonding strength between the ceramic coating 20 and the conductive ceramic substrate 10; the surface layer 22 includes a glass phase and a metal complex. The glass phase plays an antioxidant role on the surface of the ceramic coating 20. The metal complex has good high-temperature fluidity and can self-repair cracks in the ceramic coating 20. The glass phase and the metal complex together form a dense surface structure to extend the service life of the conductive ceramic 100. It should be noted that Figure 1 It is only used to illustrate the cross-sectional schematic diagram of the conductive ceramic, and does not constitute a limitation on the internal structural features of the conductive ceramic 100 .
[0038] In the present application, the conductive ceramic matrix 10 can be made of various conductive ceramic materials that can be used to prepare a heating element that does not burn. The conductive ceramic matrix 10 contains metal elements, and the metal elements include but are not limited to one or more of aluminum, magnesium and transition metals. Specifically, transition metals include but are not limited to one or more of gold, silver, copper, platinum, nickel, chromium, yttrium, cobalt, zinc, molybdenum, and manganese. The form of the metal element in the conductive ceramic matrix 10 is not limited. Specifically, the metal element form can be one or more of a metal element and a metal oxide, carbide, boride, and nitride. In one embodiment of the present application, the conductive ceramic matrix 10 includes elemental gold, elemental silver, elemental copper, elemental platinum, nickel carbide, and elemental chromium. In another embodiment of the present application, the conductive ceramic matrix 10 includes elemental copper, elemental platinum, elemental nickel, elemental yttrium, and zirconium carbide. In some embodiments, the conductive ceramic matrix 10 includes one or more of carbides, nitrides, and borides of transition metals.
[0039] In one embodiment of the present application, the bottom layer 21 is a non-glass phase, including a silicon-containing material, a boron-containing material, and a phosphate of at least one metal element. The metal element contained in the bottom layer 21 is the same as at least one metal element in the conductive ceramic substrate 10, which can reduce the difference in thermal expansion coefficient between the ceramic coating 20 and the conductive ceramic substrate 10, and at the same time improve the bonding strength between the ceramic coating 20 and the conductive ceramic substrate 10. Specifically, the phosphate of the metal element includes but is not limited to one or more of zirconium phosphate, aluminum phosphate, magnesium phosphate and yttrium phosphate. In one embodiment of the present application, the conductive ceramic substrate 10 contains metal zirconium, and the phosphate of the metal element in the bottom layer 21 includes zirconium phosphate. In another embodiment of the present application, the conductive ceramic substrate 10 contains metal zirconium and metal yttrium, and the phosphate of the metal element in the bottom layer 21 includes yttrium phosphate and zirconium phosphate.
[0040] In one embodiment of the present application, the bottom layer 21 includes a silicon-containing material. Specifically, the silicon-containing material includes but is not limited to elemental silicon, molybdenum disilicide, silicon carbide and silicon nitride. There are many types of silicon-containing materials, which are convenient and easy to obtain, have high selectivity and good chemical stability. In some embodiments of the present application, the surface layer 22 is obtained by reacting raw materials with the same composition as the bottom layer 21 in an oxidizing atmosphere. The silicon dioxide generated by oxidation of the silicon-containing material has a small thermal expansion coefficient, is insulating, and is corrosion-resistant, and can improve the performance of the ceramic coating. In one embodiment of the present application, the silicon-containing material includes molybdenum disilicide, and the metal element molybdenum is a metal element that the conductive ceramic substrate 10 may contain. When the conductive ceramic substrate 10 contains molybdenum, when the silicon-containing material of the bottom layer 21 includes molybdenum disilicide, the difference in thermal expansion coefficient between the bottom layer 21 and the conductive ceramic substrate 10 can be reduced, and the bonding between the bottom layer 21 and the conductive ceramic substrate 10 can be enhanced. In another embodiment of the present application, the silicon-containing material includes silicon carbide.
[0041] In one embodiment of the present application, the bottom layer 21 includes a boron-containing material. Specifically, the boron-containing material includes but is not limited to elemental boron, boron oxide, boron carbide and zirconium boride. Boron-containing materials can improve the strength and toughness of the bottom layer 21 and improve the oxidation resistance of the ceramic coating 20. In some embodiments of the present application, the surface layer 22 is obtained by reacting raw materials with the same composition as the bottom layer 21 in an oxidizing atmosphere. Boron oxide generated by oxidation of the boron-containing material can reduce the melting point of the surface glass phase, promote the flow of the glass phase and densify the ceramic coating. In one embodiment of the present application, the boron-containing material is boron carbide. Boron carbide has a high melting point and good chemical stability, and can improve the oxidation resistance of the ceramic coating. In another embodiment of the present application, the boron-containing material is elemental boron.
[0042] In one embodiment of the present application, the mass percentage of silicon-containing material included in the bottom layer 21 is 10%-50%, the mass percentage of boron-containing material is 10%-30%, and the mass percentage of phosphate of metal element is 30%-70%. A higher proportion of phosphate of metal element can improve the bonding strength between the bottom layer 21 and the conductive ceramic substrate 10. In some embodiments of the present application, the surface layer 22 is obtained by reacting raw materials with the same composition as the bottom layer 21 in an oxidizing atmosphere. Phosphate has a good sintering effect at high temperature. Controlling it at a higher proportion can improve the bonding effect of the coating. Silicon-containing material can be oxidized to generate silicon dioxide, and boron-containing material can generate boron oxide. The higher the proportion of boron oxide, the lower the melting point of the corresponding glass phase, and the higher the fluidity. The appropriate proportion of B and Si can form a dense glass phase. Specifically, the mass percentage of the phosphate of the metal element can be 30%, 35%, 40%, 45%, 50%, 60%, 70%, etc., the mass percentage of the silicon-containing material can be 10%, 20%, 30%, 40%, 48%, 50%, etc., and the mass percentage of the boron-containing material can be 10%, 15%, 17%, 20%, 23%, 25%, 27%, 30%, etc. In one embodiment of the present application, the bottom layer 21 includes 60% phosphate, 25% silicon-containing material and 15% boron-containing material by mass percentage. In another embodiment of the present application, the bottom layer 21 includes 50% phosphate, 20% silicon-containing material and 30% boron-containing material by mass percentage. In another embodiment of the present application, the bottom layer 21 includes 30% phosphate, 46% silicon-containing material and 24% boron-containing material by mass percentage.
[0043] In one embodiment of the present application, in the bottom layer 21, the D50 particle size of the silicon-containing material, the boron-containing material and the phosphate of the metal element is 2μm-30μm. Among them, the D50 particle size of the phosphate of the metal element is 4μm-5μm, the D50 particle size of the silicon-containing material is 20μm-30μm, and the D50 particle size of the boron-containing material is 2μm-10μm. The particle size of the phosphate of the metal element is small and can be filled between large-sized particles such as silicon-containing materials and boron-containing materials, and the resulting ceramic coating 20 has good uniformity. Specifically, the particle size of the phosphate D50 of the metal element can be 4μm, 4.5μm, 4.8μm, 5μm, etc., the particle size of the silicon-containing material D50 can be 20μm, 22μm, 23μm, 25μm, 27μm, 29μm, 30μm, etc., and the particle size of the boron-containing material D50 can be 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, etc. In one embodiment of the present application, the particle size of the phosphate D50 of the metal element is 4μm, the particle size of the silicon-containing material D50 is 20μm, and the particle size of the boron-containing material D50 is 2μm. In another embodiment of the present application, the particle size of the phosphate D50 of the metal element is 4.5μm, the particle size of the silicon-containing material D50 is 25μm, and the particle size of the boron-containing material D50 is 7μm.
[0044] In one embodiment of the present application, the thickness of the bottom layer 21 is 20μm-65μm. The metal element contained in the bottom layer 21 is the same as at least one metal element in the conductive ceramic substrate 10, which can reduce the thermal expansion difference between the ceramic coating 20 and the conductive ceramic substrate 10. The bottom layer 21 with a certain thickness can further alleviate the thermal mismatch effect between the conductive ceramic substrate 10 and the surface layer 22, and prevent the ceramic coating 20 from cracking during use. Specifically, the thickness of the bottom layer 21 can be 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, etc. In one embodiment of the present application, the thickness of the bottom layer 21 is 30μm. In another embodiment of the present application, the thickness of the bottom layer 21 is 60μm.
[0045] In one embodiment of the present application, the surface layer 22 includes a glass phase and a metal complex, and the glass phase and the metal complex in the surface layer 22 are obtained by reacting the same silicon-containing material, boron-containing material and at least one metal element phosphate as the bottom layer 21 in an oxidizing atmosphere. That is, before the oxidation reaction, the bottom layer 21 and the surface layer 22 have the same components and are prepared as a whole. After the oxidation reaction, the surface layer 22 contains at least one metal element, as well as silicon, boron, phosphorus and oxygen, wherein the metal element contained in the surface layer 22 is the same as the metal element contained in the bottom layer 21. The glass phase in the surface layer 22 is obtained by an oxidation reaction of silicon-containing materials and metal element phosphates. Since different positions in the surface layer 22 are exposed to different oxygen contents, their oxidation degrees are also different. The glass phase content on the side of the surface layer 22 away from the conductive ceramic substrate 10 is greater than the glass phase content on the side close to the conductive ceramic substrate 10. The outermost side of the ceramic coating 20 is completely exposed to the oxygen atmosphere, and the silicon-containing material is almost completely oxidized, and combined with the phosphate of the metal element to form a glass phase. At this time, the outermost side of the surface layer 22 away from the conductive ceramic substrate 10 is a completely vitrified phase, and its glass phase content reaches a peak value. As the contact between oxygen and the inner side of the surface layer 22 begins to weaken, the silicon-containing material is partially oxidized, and the content of the formed glass phase gradually decreases. The glass phase in the surface layer 22 can improve the oxidation resistance and density of the ceramic coating 20. The distribution mode of more outside and less inside can alleviate the structural deformation caused by the thermal expansion of the conductive ceramic 100 during heating, further alleviate the thermal mismatch effect of the conductive ceramic 100, and improve the service life of the conductive ceramic 100. It can be understood that the composition of the glass phase is determined by the silicon-containing material and the phosphate of the metal element. Using different metal element phosphates, the glass phase components formed are different. Specifically, the glass phase can be ZrSi2O5, YSi2O5, AlSiO3, MgSiO3, ZrSiB3O7, ZrSiB4O7, etc. In one embodiment of the present application, the glass phase component of the surface layer 22 is ZrSi2O5. In another embodiment of the present application, the glass phase component of the surface layer 22 is YSi2O5.
[0046] In one embodiment of the present application, the metal complex of the surface layer 22 includes metal elements, phosphorus elements and boron elements. Similar to the formation of the glass phase, the metal complex is obtained by an oxidation reaction between a boron-containing material and a phosphate of the metal element. The boron-containing material is converted into boron oxide after oxidation. Boron oxide has excellent fluidity and can dissolve the phosphate of the metal element and combine with it to form a metal complex. In the surface layer 22, the metal complex and the glass phase have content distributions with opposite trends. The metal complex content on the side close to the conductive ceramic substrate 10 is greater than the metal complex content on the side away from the conductive ceramic substrate 10. In addition, since boron oxide has high-temperature fluidity, the synthesized metal complex can flow with the flow of boron oxide during the heating process, so cracks in the ceramic coating 20 caused by differences in thermal expansion coefficients can be repaired, so that the ceramic coating 20 has the ability to self-repair cracks. Please refer to Figure 2 , Figure 2 A schematic diagram of the formation mechanism of a metal complex provided in one embodiment of the present application, wherein oxygen atoms in the phosphate of the metal element and boron atoms in the boron oxide are chemically bonded to form a B-ZrP metal complex, and the B-ZrP metal complex follows the flow of the boron oxide to repair cracks in the ceramic coating 20.
[0047] In one embodiment of the present application, the thickness of the surface layer 22 is 10μm-35μm, wherein the content distribution of the glass phase is more outside and less inside, which improves the antioxidant ability and density of the ceramic coating 20, can alleviate the thermal mismatch effect caused by the large difference in thermal expansion coefficient between the ceramic coating 20 and the conductive ceramic substrate 10, and the metal complex with fluidity can self-repair the surface cracks of the ceramic coating 20 and improve the service life of the conductive ceramic 100. Specifically, the thickness of the surface layer 22 can be 10μm, 15μm, 17μm, 20μm, 24μm, 28μm, 30μm, 35μm, etc. In one embodiment of the present application, the thickness of the surface layer 22 is 10μm-20μm. In another embodiment of the present application, the thickness of the surface layer 22 is 15μm-35μm.
[0048] In one embodiment of the present application, the porosity of the bottom layer 21 is greater than the porosity of the surface layer 22, that is, the bottom layer 21 is relatively porous compared to the surface layer 22, and the pore structure existing in the bottom layer 21 can alleviate the structural deformation caused by the thermal expansion of the conductive ceramic matrix 10, and can further reduce the adverse effects caused by the thermal mismatch effect.
[0049] In the present application, the thickness of the ceramic coating 20 is 30 μm-100 μm. The ceramic coating 20 with a special structure improves the bonding strength and thermal matching with the conductive ceramic substrate 10, which is beneficial to enhance the anti-oxidation performance and structural stability of the conductive ceramic 100. Specifically, the thickness of the ceramic coating 20 can be 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, etc. In one embodiment of the present application, the thickness of the ceramic coating 20 can be 35 μm-60 μm. In another embodiment of the present application, the thickness of the ceramic coating 20 can be 40 μm-85 μm.
[0050] In one embodiment of the present application, the electrical conductivity of the ceramic coating 20 is less than or equal to 10 -12 S / cm. That is, the ceramic coating 20 has a high resistivity and poor conductivity, which can prevent the electric energy loss caused by the heating of the conductive ceramic substrate 10. Specifically, the electrical conductivity of the ceramic coating 20 can be less than or equal to 10 -12 S / cm, less than or equal to 10 -13 S / cm, less than or equal to 5×10 -13 S / cm, less than or equal to 10 -14 S / cm, less than or equal to 10 -17 S / cm, etc. In one embodiment of the present application, the electrical conductivity of the ceramic coating 20 is less than or equal to 10 -13 In another embodiment of the present application, the electrical conductivity of the ceramic coating 20 is less than or equal to 4×10 -15 S / cm.
[0051] In one embodiment of the present application, the mass change rate of the conductive ceramic 100 after being heated at 300-1000°C for 2h in the atmosphere is less than or equal to 0.1%. The mass change rate is the ratio of the mass change of the conductive ceramic 100 before and after heating to the mass of the conductive ceramic 100 before heating. The mass of the conductive ceramic 100 before heating is m1, and the mass of the conductive ceramic 100 after heating is m2. The mass change rate = (m1-m2) / m1×100%. In the atmosphere, the conductive ceramic 100 is kept at a certain temperature for a period of time, and its mass change rate is observed. The smaller the mass change rate, the more difficult it is for the components in the conductive ceramic substrate 10 to undergo oxidation volatilization, and the stronger the antioxidant capacity of its ceramic coating 20. Specifically, the heating temperature includes but is not limited to 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C and 1000°C, and the mass change rate may be less than or equal to 0.1%, less than or equal to 0.08%, less than or equal to 0.06%, less than or equal to 0.03%, etc. In one embodiment of the present application, the mass change rate of the conductive ceramic 100 heated at 700°C for 2h in the atmosphere is less than or equal to 0.08%. In one embodiment of the present application, the mass change rate of the conductive ceramic 100 heated at 500°C for 2h in the atmosphere is less than or equal to 0.06%.
[0052] In one embodiment of the present application, the bonding strength between the conductive ceramic substrate 10 and the ceramic coating 20 is greater than or equal to 5 MPa. Figure 3 , Figure 3 This is a schematic diagram of the bonding strength test of the ceramic coating 20 on the surface of the conductive ceramic 100 in one embodiment of the present application. The surface of the conductive ceramic substrate 10 is provided with a ceramic coating 20, and the ceramic coating 20 is bonded to the test column 40 of the tensile testing machine through an adhesive 30. The test group is placed on a suitable tensile testing machine to measure the bonding strength. The bonding strength is the maximum tensile force that the ceramic coating 20 and the conductive ceramic substrate 10 can withstand without separation. The greater the bonding strength between the conductive ceramic substrate 10 and the ceramic coating 20, the stronger the bonding force between the ceramic coating 20 and the conductive ceramic substrate 10, and the better the mechanical properties of the conductive ceramic 100. Specifically, the bonding strength between the conductive ceramic substrate 10 and the ceramic coating 20 can be greater than or equal to 5MPa, greater than or equal to 6MPa, greater than or equal to 7MPa, greater than or equal to 9MPa, greater than or equal to 10MPa, etc. In one embodiment of the present application, the bonding strength between the conductive ceramic substrate 10 and the ceramic coating 20 is greater than or equal to 6MPa. In another embodiment of the present application, the bonding strength between the conductive ceramic substrate 10 and the ceramic coating 20 is greater than or equal to 7 MPa.
[0053] In one embodiment of the present application, the porosity of the conductive ceramic 100 is less than or equal to 0.1%. The porosity is the ratio of the volume v1 of the open pores to the volume v2 of the conductive ceramic 100. The porosity = v1 / v2×100%. The lower the porosity, the higher the density of the ceramic coating 20 and the better the density of the conductive ceramic 100. Specifically, the porosity of the conductive ceramic 100 may be less than or equal to 0.1%, less than or equal to 0.09%, less than or equal to 0.07%, less than or equal to 0.05%, less than or equal to 0.03%, etc. In one embodiment of the present application, the porosity of the conductive ceramic 100 is less than or equal to 0.08%. In another embodiment of the present application, the porosity of the conductive ceramic 100 is less than or equal to 0.05%.
[0054] The present application provides a method for preparing a conductive ceramic, which can prepare the conductive ceramic in any of the above embodiments. Figure 4 , Figure 4 A flow chart of a method for preparing a conductive ceramic 100 provided in one embodiment of the present application includes:
[0055] S101: preparing a mixed slurry from a silicon-containing material, a boron-containing material and a phosphate of a metal element, and coating the mixed slurry on the surface of a conductive ceramic substrate 10;
[0056] S102 : performing an oxidation treatment on the conductive ceramic substrate 10 coated with the mixed slurry to obtain a conductive ceramic 100 having a ceramic coating 20 .
[0057] The preparation method of the conductive ceramic 100 provided in the present application is simple and easy to operate, and can produce a conductive ceramic 100 with excellent antioxidant properties and strong self-healing ability, which is conducive to the widespread use of the conductive ceramic 100.
[0058] In S101 , the phosphate of the metal element, the silicon-containing material and the boron-containing material are weighed and proportioned according to mass percentage, and then mixed with a solvent to obtain a mixed slurry. The obtained mixed slurry is coated on the conductive ceramic substrate 10 .
[0059] In the present application, silicon-containing materials, boron-containing materials and phosphates of metal elements can be prepared by using powder as raw materials for mixed slurry. The particle size of the raw powder has a certain influence on the density of the ceramic coating 20. The smaller the powder particle size, the higher the density of the ceramic coating 20 and the better the antioxidant performance. In one embodiment of the present application, the D50 particle size of the above-mentioned raw powder is 2μm-30μm. Among them, the D50 particle size of the phosphate powder of the metal element is 4μm-5μm, the D50 particle size of the silicon-containing material powder is 20μm-30μm, and the D50 particle size of the boron-containing material powder is 2μm-10μm. The raw powder with a powder particle size within this range has strong controllability and is easy to obtain a powder with an ideal particle size after processing. At the same time, the phosphate powder of the metal element has a small particle size and can be filled between large-sized particles such as silicon-containing materials and boron-containing materials, so that the uniformity of the mixed slurry is improved, and the obtained ceramic coating 20 has good uniformity. Moreover, the phosphate of the metal element is dispersed in the silicon-containing material and the boron-containing material, which can accelerate the process of the subsequent oxidation reaction and shorten the oxidation reaction time. Specifically, the particle size of the phosphate powder D50 of the metal element can be 4μm, 4.5μm, 4.8μm, 5μm, etc., the particle size of the silicon-containing material powder D50 can be 20μm, 22μm, 23μm, 25μm, 27μm, 29μm, 30μm, etc., and the particle size of the boron-containing material powder D50 can be 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, etc. In one embodiment of the present application, the particle size of the phosphate powder D50 of the metal element is 4μm, the particle size of the silicon-containing material powder D50 is 20μm, and the particle size of the boron-containing material powder D50 is 2μm. In another embodiment of the present application, the particle size D50 of the phosphate powder of the metal element is 4.5 μm, the particle size D50 of the silicon-containing material powder is 25 μm, and the particle size D50 of the boron-containing material powder is 7 μm.
[0060] In one embodiment of the present application, the mass percentage of silicon-containing material in the raw material powder is 10%-50%, the mass percentage of boron-containing material is 10%-30%, and the mass percentage of phosphate of metal element is 30%-70%. Phosphate of metal element has good high temperature sintering performance, and a higher proportion of metal element phosphate can improve the bonding strength between ceramic coating 20 and conductive ceramic substrate 10. During oxidation reaction, the appropriate proportion of boron-containing material and silicon-containing material can reduce the glass phase formation temperature and obtain a high-density ceramic coating 20. Specifically, the mass percentage of phosphate of metal element can be 30%, 35%, 40%, 45%, 50%, 60%, 70%, etc., the mass percentage of silicon-containing material can be 10%, 20%, 30%, 40%, 48%, 50%, etc., and the mass percentage of boron-containing material can be 10%, 15%, 17%, 20%, 23%, 25%, 27%, 30%, etc. In one embodiment of the present application, the raw material powder includes 70% by mass of phosphate, 20% by mass of silicon-containing material and 10% by mass of boron-containing material, and a ceramic coating with excellent oxidation resistance can be obtained. In another embodiment of the present application, the raw material powder includes 50% by mass of phosphate, 20% by mass of silicon-containing material and 30% by mass of boron-containing material. In another embodiment of the present application, the raw material powder includes 30% by mass of phosphate, 46% by mass of silicon-containing material and 24% by mass of boron-containing material.
[0061] In one embodiment of the present application, the solvent of the mixed slurry can be a relatively volatile organic solvent. An organic solvent with good volatility can accelerate the formation of the ceramic coating 20. Specifically, the solvent can be ethyl acetate, methanol, pine alcohol, butyl carbitol acetate, ethanol, etc. In the mixed slurry, the total content of phosphate, silicon-containing material and boron-containing material is 5g / mL-10g / mL, specifically, it can be 5g / mL, 6g / mL, 7g / mL, 8g / mL, 9g / mL, 10g / mL, etc. When the total content of phosphate, silicon-containing material and boron-containing material in the mixed slurry is within the range of 5g / mL-10g / mL, it is beneficial to obtain a mixed slurry with a more suitable viscosity, improve the uniformity and density of the ceramic coating 20, and the mechanical properties. In one embodiment of the present application, the solvent is ethanol, and the total content of phosphate, silicon-containing material and boron-containing material in the mixed slurry is 5g / mL. In another embodiment of the present application, the solvent is ethyl acetate, and the total content of phosphate, silicon-containing material and boron-containing material in the mixed slurry is 8 g / mL.
[0062] In the present application, the preparation method of the mixed slurry includes but is not limited to ball milling, stirring and grinding, which can be selected according to the specific requirements of the required ceramic coating 20. In one embodiment of the present application, the preparation method of the mixed slurry adopts a ball milling process, which improves the uniformity of the mixed slurry, reduces the particle size of the raw material powder, and is conducive to improving the density of the ceramic coating 20. In one embodiment of the present application, the ball milling time of the mixed slurry is 1h-5h, and the ball milling speed is 200r / min-400r / min. Specifically, the ball milling time can be 1h, 2h, 3h, 4h, 5h, etc., and the ball milling speed can be 200r / min, 250r / min, 300r / min, 350r / min, 400r / min, etc. In one embodiment of the present application, the ball milling time of the mixed slurry is 2h, and the ball milling speed is 340r / min. In another embodiment of the present application, the ball milling time of the mixed slurry is 1h, and the ball milling speed is 280r / min.
[0063] In one embodiment of the present application, the mixed slurry is coated on the surface of the conductive ceramic substrate 10. Specifically, the coating method includes but is not limited to brushing, shower coating, dipping or spraying, etc., which can be selected according to the actual application of the required ceramic coating 20. In one embodiment of the present application, the coating method used is spraying, which can improve the coating efficiency and greatly improve the adhesion of the coating. In another embodiment of the present application, the coating method used is dipping.
[0064] In S102, the conductive ceramic substrate 10 containing the coating mixed slurry is subjected to oxidation treatment to obtain a ceramic coating 20. The surface layer 22 in contact with oxygen undergoes an oxidation reaction, and the oxide combines with the phosphate of the metal element to obtain a glass phase and a metal complex, respectively. The porous bottom layer 21 enhances the bonding strength between the ceramic coating 20 and the conductive ceramic substrate 10, and alleviates the thermal mismatch effect between the ceramic coating 20 and the conductive ceramic substrate 10; the glass phase with more outside and less inside improves the oxidation resistance and density of the ceramic coating 20, and further alleviates the thermal mismatch effect of the conductive ceramic 100. At the same time, the metal complex with fluidity can repair cracks in the ceramic coating 20, enhance the structural stability of the conductive ceramic 100, and improve the service life of the conductive ceramic 100.
[0065] In one embodiment of the present application, the conductive ceramic substrate 10 containing the coating slurry is subjected to oxidation treatment, the oxidation treatment time is 1h-5h, and the oxidation treatment temperature is 1000℃-1500℃. After the oxidation treatment, a dense ceramic coating 20 surface can be formed, which can prevent the intrusion of water vapor during the use of the conductive ceramic 100 and extend the service life of the conductive ceramic 100. Controlling the appropriate oxidation treatment temperature and time is conducive to making the ceramic coating 20 have a higher density, improving oxidation resistance, and saving time and energy costs. Specifically, the oxidation treatment time can be 1h, 1.5h, 2h, 2.5h, 3h, 4h, 4.5h, 5h, etc., and the oxidation treatment temperature can be 1000℃, 1100℃, 1200℃, 1300℃, 1400℃, 1500℃, etc. In one embodiment of the present application, the oxidation treatment temperature is 1200℃, and the oxidation treatment time is 2h, which can accelerate the oxidation rate and shorten the oxidation process. In another embodiment of the present application, the temperature of the oxidation treatment is 1000° C., and the time of the oxidation treatment is 4 hours. In another embodiment of the present application, the temperature of the oxidation treatment is 1500° C., and the time of the oxidation treatment is 1 hour.
[0066] The present application provides a heating element, the heating element for heating without burning includes the conductive ceramic 100 in any one of the above embodiments, which is beneficial to improving the performance and life of the heating element. The present application does not limit the shape and application of the heating element.
[0067] The present application also provides an electronic cigarette atomizer, which includes the heating element in any one of the above-mentioned embodiments, which is conducive to improving the market competitiveness of the electronic cigarette atomizer.
[0068] The effect of the technical solution of the present application is further illustrated below through specific examples.
[0069] Example 1
[0070] Weigh 10g of mixed powder, the mixed powder includes 70% by mass of zirconium phosphate, whose D50 particle size is 4μm, 20% by mass of molybdenum disilicide, whose D50 particle size is 20μm, and 10% by mass of boron carbide, whose D50 particle size is 2μm, add 5mL of ethanol, and mix by ball milling. The ball milling speed is 340r / min, and the ball milling time is 2h to obtain a mixed slurry. The mixed slurry is evenly coated on the surface of the conductive ceramic substrate by spraying, the spraying pressure is 0.4MPa, and the spraying distance is 30cm. The conductive ceramic substrate coated with the mixed slurry is oxidized at a temperature of 1200℃ and a time of 2h to obtain a conductive ceramic with a ceramic coating, wherein the thickness of the ceramic coating is 90μm and the thickness of the surface layer is 30μm.
[0071] Figure 5This is a cross-sectional scanning electron microscope image of the conductive ceramic prepared in Example 1 of the present application. Figure 6 for Figure 5 The X-ray diffraction analysis results of the area in the middle dotted box; Figure 7 for Figure 5 Line scanning analysis results of oxygen element in ceramic coating. Figure 5 It can be clearly seen that the conductive ceramic includes a conductive ceramic substrate 10 and a bottom layer 21 and a surface layer 22 formed on the conductive ceramic substrate 10 . Figure 6 This indicates that the surface layer 22 contains a ZrSi2O5 glass phase. Figure 7 The figure is the distribution result of oxygen element by line scanning from the surface of the surface layer 22 to the depth of 34 μm using a scanning electron microscope. The direction indicated by the arrow is the line scanning direction. Figure 7 It can be seen that the oxygen content in the bottom layer 21 is relatively low, and in the surface layer 22, the oxygen content gradually increases from the bottom layer to the surface layer. Since the increase in oxygen element in the surface layer 22 relative to the bottom layer 21 is mainly due to the formation of the glass phase, it can be seen from the distribution of oxygen elements that the glass phase content in the surface layer 22 shows an increasing trend, and the glass phase is distributed with more on the outside and less on the inside.
[0072] Fig. 8A and Figure 8B The following are the scanning electron microscope images of the ceramic coating crack before and after repair. Fig. 8A This is a surface scanning electron microscope image of a ceramic coating after a crack was created on the surface using a microhardness tester. Figure 8B For the general Fig. 8A The ceramic coating surface scanning electron microscope image obtained after the ceramic coating after the crack was repaired by heat treatment at 500℃ for 1h-2h is compared with Fig. 8A and Figure 8B It can be seen that after heat treatment, the cracks basically disappeared, indicating that the ceramic coating has the ability of crack self-healing.
[0073] Example 2
[0074] The difference from Example 1 is that the mixed powder includes 50% by mass of zirconium phosphate, 34% by mass of molybdenum disilicide and 16% by mass of boron carbide.
[0075] Example 3
[0076] The difference from Example 1 is that the mixed powder includes 30% by mass of zirconium phosphate, 46% by mass of molybdenum disilicide and 24% by mass of boron carbide.
[0077] Example 4
[0078] The difference from Example 1 is that the mixed powder includes 70% by mass of zirconium phosphate, 15% by mass of molybdenum disilicide and 15% by mass of boron carbide.
[0079] Example 5
[0080] The difference from Example 1 is that the mixed powder includes 70% by mass of zirconium phosphate, 10% by mass of molybdenum disilicide and 20% by mass of boron carbide.
[0081] Example 6
[0082] The difference from Example 1 is that the mixed powder includes 70% by mass of yttrium phosphate, 20% by mass of silicon nitride and 10% by mass of elemental boron.
[0083] Example 7
[0084] The difference from Example 1 is that the mixed powder includes 70% by mass of aluminum phosphate.
[0085] Example 8
[0086] The difference from Example 1 is that in the mixed powder, the D50 particle size of zirconium phosphate is 5 μm, the D50 particle size of molybdenum disilicide is 25 μm, and the D50 particle size of boron carbide is 7 μm.
[0087] Example 9
[0088] The difference from Example 1 is that the temperature of the oxidation treatment is 1000°C.
[0089] Example 10
[0090] The difference from Example 1 is that the temperature of the oxidation treatment is 1500°C.
[0091] Embodiment 11
[0092] The difference from Example 1 is that the oxidation treatment time is 1 hour.
[0093] Example 12
[0094] The difference from Example 1 is that the oxidation treatment time is 5 h.
[0095] Comparative Example 1
[0096] The difference from Example 1 is that the mixed powder includes 60% by mass of zirconium phosphate and 40% by mass of borosilicate glass powder. The borosilicate glass powder includes 62.5% by mass of silicon oxide and 37.5% by mass of boron oxide, wherein the borosilicate glass powder is prepared by water quenching and smelting.
[0097] Performance Testing
[0098] The conductive ceramics prepared in the above Examples 1-12 and Comparative Example 1 were tested for bonding strength according to GB / T5210-2006 “Adhesion test for paints and varnishes by pull-off method”. The test results are shown in Table 1.
[0099] The conductive ceramics prepared in the above-mentioned Examples 1-12 and Comparative Example 1 were tested for their porosity using the Archimedean drainage method. The test results are shown in Table 1.
[0100] The conductivity of the conductive ceramics prepared in the above Examples 1-12 and Comparative Example 1 was tested by a direct current method. The current was measured by a multimeter and the conductivity was calculated based on the sample size. The test results are shown in Table 1.
[0101] The conductive ceramics prepared in the above Examples 1-12 and Comparative Example 1 were kept at 300°C-1000°C for 2h to test the mass change of the conductive ceramics before and after, and the mass change rate was calculated. The test results are shown in Table 2.
[0102] Table 1 Performance test results
[0103]
[0104]
[0105] Table 2 Quality change rate test results
[0106] Quality change rate (%) 300℃ 500℃ 700℃ 1000℃ Example 1 0.03 0.06 0.08 0.1 Example 2 0.05 0.12 0.17 0.56 Example 3 0.06 0.25 0.56 0.77 Example 4 0.04 0.09 0.11 0.20 Example 5 0.04 0.15 0.32 0.47 Example 6 0.08 0.35 0.47 0.62 Example 7 0.03 0.21 0.65 0.90 Example 8 0.08 0.08 0.10 0.19 Example 9 0.09 0.35 0.59 0.86 Example 10 0.05 0.11 0.16 0.23 Embodiment 11 0.06 0.36 0.57 0.82 Example 12 0.03 0.13 0.22 0.35 Comparative Example 1 0.10 0.36 0.79 1.0
[0107] Combining the data in Table 1 and Table 2, it can be seen that compared with Comparative Example 1, the conductive ceramics provided in Examples 1-12 of the present application have a surface ceramic coating with higher bonding strength, higher density, better insulation performance and better antioxidant ability, thereby avoiding the shedding of the conductive ceramic coating and extending the service life of the conductive ceramic; reducing the mass loss and power loss generated during the heating process of the conductive ceramic.
[0108] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. A conductive ceramic, characterized in that: It includes a conductive ceramic substrate and a ceramic coating arranged on the surface of the conductive ceramic substrate, the conductive ceramic substrate includes metal elements, and the ceramic coating includes a bottom layer and a surface layer stacked in sequence on the surface of the conductive ceramic substrate; the bottom layer includes a silicon-containing material, a boron-containing material and at least one phosphate of the metal element, and the surface layer includes a glass phase and a metal complex.
2. The conductive ceramic according to claim 1, characterized in that The surface layer contains at least one of the metal elements, as well as silicon, boron, phosphorus and oxygen.
3. The conductive ceramic according to claim 1, characterized in that The metal element contained in the surface layer is the same as the metal element contained in the base layer.
4. The conductive ceramic according to claim 1, characterized in that In the surface layer, the glass phase content on the side away from the conductive ceramic substrate is greater than the glass phase content on the side close to the conductive ceramic substrate, and the metal complex content on the side close to the conductive ceramic substrate is greater than the metal complex content on the side away from the conductive ceramic substrate.
5. The conductive ceramic according to claim 1, characterized in that The metal element includes one or more of aluminum, magnesium and transition metals; the transition metal includes one or more of gold, silver, copper, platinum, nickel, chromium, yttrium, cobalt, zinc, molybdenum and manganese; The silicon-containing material includes one or more of elemental silicon, molybdenum disilicide, silicon carbide and silicon nitride; The boron-containing material includes one or more of elemental boron, boron oxide, boron carbide, boron nitride and zirconium boride.
6. The conductive ceramic according to claim 1, characterized in that In the bottom layer, the mass percentage of the silicon-containing material is 10%-50%, the mass percentage of the boron-containing material is 10%-30%, and the mass percentage of the phosphate of the metal element is 30%-70%.
7. The conductive ceramic according to claim 1, characterized in that: The glass phase and the metal complex of the surface layer are obtained by reacting the same silicon-containing material and boron-containing material as the bottom layer and at least one phosphate of the metal element in an oxidizing atmosphere.
8. The conductive ceramic according to claim 1, characterized in that The thickness of the ceramic coating is 30 μm-100 μm, the thickness of the surface layer is 10 μm-35 μm, and the thickness of the bottom layer is 20 μm-65 μm.
9. The conductive ceramic according to claim 1, characterized in that The electrical conductivity of the ceramic coating is less than or equal to 10 - 12 S / cm; the bonding strength between the conductive ceramic substrate and the ceramic coating is greater than or equal to 5MPa; the porosity of the conductive ceramic is less than or equal to 0.1%; the mass change rate of the conductive ceramic after heating at 300°C-1000°C for 2h is less than or equal to 0.1%.
10. A method for preparing a conductive ceramic, characterized in that: include: Prepare a mixed slurry with silicon-containing material, boron-containing material and phosphate of metal elements, and apply the mixed slurry on the surface of the conductive ceramic substrate; The conductive ceramic substrate coated with the mixed slurry is subjected to oxidation treatment to obtain a conductive ceramic with a ceramic coating.
11. The preparation method according to claim 10, characterized in that: The temperature of the oxidation treatment is 1000° C.-1500° C., and the time of the oxidation treatment is 1 h-5 h.
12. A heat-not-burn heating element, characterized in that: The heat-without-combustion heating element comprises the conductive ceramic described in any one of claims 1 to 9 or the conductive ceramic prepared by the preparation method described in any one of claims 10 to 11.
13. An electronic cigarette, characterized in that: The electronic cigarette comprises the heat-not-burn heating element according to claim 12.